INVESTIGATION OF THE PHYSICOCHEMICAL AND BACTERIOLOGICAL QUALITIES OF OKOKPON RIVER, EDO STATE, NIGERIA FOR ITS PORTABILITY STATUS (FUDMA JOURNAL OF SCIENCES, 2023)
Water occupies about 75% of the earth surface, yet access to portable water remains the most daunting task for everyone due to its frequent contamination. The physicochemical and microbiological characteristics of water samples from Okokpon River was determined on a monthly basis between October, 2011 and May, 2012. Routine laboratory procedures were employed in water analyses. The physicochemical parameters recorded were all lower than SON and WHO limit except turbidity (1.73±0.33 to 7.42±1.51NTU), iron (0.76±0.15 to 1.35±0.27mg/l) and lead (0.76±0.15 to 1.35±0.27). Electrical conductivity, total dissolved solid, alkalinity, potassium and total hardness showed significant difference (p < 0.05) at the downstream. The heterotrophic bacterial and fungal counts ranged from 2.16 to 5.89 ×105cfu/ml and 3.01 to 3.69×105cfu/ml respectively with the highest at downstream which also had a significant difference for the heterotrophic bacterial counts (P
Keywords: Coliform, Okokpon River, Plasmid, Set limits, Turbidity, Water Regulatory Agencie